Implementation of UAV for Pavement Functional Performance Assesment - Astor, Yackob; Utami, Retno; Nabesima, Yasuyuki; Sihombing, Atmy Verani Rouly (International Journal of Sustainable Construction Engineering and Technology, 2023)
Pavement conditions could be degraded throughout its service life. Hence, a pavement management system is needed to ensure pavement performance according to its design life. To support a reliable pavement, a pavement condition survey needs to be conducted most effective and practical way. One of the technologies used in pavement condition surveys is the Unmanned Aerial Vehicle (UAV) or known as drone. The use of UAVs for road maintenance will reduce the cost and time and with the 3D model, the accuracy level is at the centimeter level which indicates UAVs are an excellent and promising tool for road work. In this study, a PCI method of pavement condition evaluation will be used to assess pavement through both manually surveyed and 3D model calculation with the use of Agisoft application. Later on, statistical test will be carried out such as ANOVA and correlation to determine the relationship between pavement condition obtained from two different survey method as well as the comparison in identifying pavement distress, PCI value and pavement condition. As a result, those two methods can identify identical types of damage, with a fairly high percentage of > 60%. While, manual method could identify a higher percentage of degree of severity than 3D model with the help of application. The manual of pavement condition assessment can identify in more detail than the Agisoft Metashape application. Based on statistical tests, the two methods used show a close and unidirectional relationship.